2020
DOI: 10.1073/pnas.1921878117
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 mediates axon development by regulating Frizzled3 phosphorylation and growth cone–growth cone communication

Abstract: Axon–axon interactions are essential for axon guidance during nervous system wiring. However, it is unknown whether and how the growth cones communicate with each other while sensing and responding to guidance cues. We found that the Parkinson’s disease gene, leucine-rich repeat kinase 2 (LRRK2), has an unexpected role in growth cone–growth cone communication. The LRRK2 protein acts as a scaffold and induces Frizzled3 hyperphosphorylation indirectly by recruiting other kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Subsequent work showed that the function of Wnts in guiding axons along the A-P axis is conserved in a number of animal species, including rodents, chick, zebrafish, and Caenorhabditis elegans , 40 45 as well as the function in topographic mapping in Drosophila visual system. 46 Wnts attract axons via a non-canonical pathway, planar cell polarity pathway 40 , 47 51 but repel axons which express Ryk as a Wnt coreceptor. 38 , 39 For more detailed discussions about how planar cell polarity pathway mediate Wnt functions in growth cone guidance, please read another recent reviews.…”
Section: Targeting Axon Guidance To Promote Functional Recoverymentioning
confidence: 99%
“…Subsequent work showed that the function of Wnts in guiding axons along the A-P axis is conserved in a number of animal species, including rodents, chick, zebrafish, and Caenorhabditis elegans , 40 45 as well as the function in topographic mapping in Drosophila visual system. 46 Wnts attract axons via a non-canonical pathway, planar cell polarity pathway 40 , 47 51 but repel axons which express Ryk as a Wnt coreceptor. 38 , 39 For more detailed discussions about how planar cell polarity pathway mediate Wnt functions in growth cone guidance, please read another recent reviews.…”
Section: Targeting Axon Guidance To Promote Functional Recoverymentioning
confidence: 99%
“…To ask whether and how Vangl2 may negatively regulate synapse numbers, we established an assay to test the intercellular PCP complex, similar to the “transcellular interaction assay” 33 . We co-transfected Frizzled3 (HA-tagged) and Celsr3 (untagged) in one dish of HEK293T cells and transfected Celsr3 (Flag-tagged) and Vangl2 in another.…”
Section: Resultsmentioning
confidence: 99%
“…Mice lacking Celsr exhibit impaired PCP signalling and hyperphosphorylated Fzd3 ( Wang and Nathans, 2007 ; Onishi et al, 2013 ). In addition, a recent study showed that both loss-of-function of leucine-rich repeat kinase 2 (LRRK2) and gain-of-function of mutated LRRK2 lacking kinase activity showed anterior–posterior guidance errors after midline crossing in vivo ( Onishi et al, 2020 ). Furthermore, they identified LRRK2 as a new protein which both directly phosphorylates Fzd3 on threonine 598 (T598) and indirectly promotes Dvl1-induced Fzd3 hyperphosphorylation by acting as a scaffold and recruiting other kinases ( Onishi et al, 2020 ).…”
Section: How Ptms Determine the Function Of Frizzled Receptorsmentioning
confidence: 99%
“…In addition, a recent study showed that both loss-of-function of leucine-rich repeat kinase 2 (LRRK2) and gain-of-function of mutated LRRK2 lacking kinase activity showed anterior–posterior guidance errors after midline crossing in vivo ( Onishi et al, 2020 ). Furthermore, they identified LRRK2 as a new protein which both directly phosphorylates Fzd3 on threonine 598 (T598) and indirectly promotes Dvl1-induced Fzd3 hyperphosphorylation by acting as a scaffold and recruiting other kinases ( Onishi et al, 2020 ). Overall, hypo- or non-phosphorylated Fzd3 is required for PCP signalling and for growth cone guidance in vivo ( Table 1 ; Shafer et al, 2011 ; Onishi et al, 2013 , 2020 ).…”
Section: How Ptms Determine the Function Of Frizzled Receptorsmentioning
confidence: 99%
See 1 more Smart Citation